Experiences of family members caring for tuberculosis patients at home at Vhembe district of the Limpopo Province - Joyce T. Sukumani; Rachel T. Lebese; Lunic B. Khoza; Patrone R. Risenga (AOSIS, 2012)
Tuberculosis (TB) is a potentially serious infectious disease which enters the body by inhalation and usually affects the lungs. TB is ranked amongst the leading infectious diseases worldwide, and in South Africa (SA) it has become an epidemic, because of its high prevalence. There are multiple factors that were found to attribute to the existence and spread of this disease. The purpose of this study was to explore and describe experiences of family members caring for TB patients at home, in the Vhembe District of the Limpopo Province. The study was qualitative, explorative, descriptive, phenomenological and contextual in nature. The population group selected for the study all comprised of family members caring for tuberculosis patients at home in Tshifulanani village. A purposive sampling method was applied in the study. Data were collected through semi-structured interviews guided by three questions. Tech's eight steps of data analysis were followed. Measures to ensure trustworthiness and ethical issues were observed. The results of the study revealed that family members experienced difficulties when they care for TB patients at home. These difficulties included providing food, attending to hygiene needs, the lack of equipment, financial constraints as well as physical and psychological exhaustion. Recommendations were made concerning the provision food, attending to hygiene needs, assisting in the administration of medication, nursing practice and policy making.